Geoecological Characteristics Of Namangan Region Under Climate Change Conditions - Abdurakhmanov, Sohibjon; Dehqonboyeva, Zaynabxon; Urmanova, Shodiyona (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the geoecological characteristics of the Namangan region under the conditions of climate change. It examines processes such as rising temperatures, changes in precipitation levels, depletion of water resources, and soil degradation within the region. The study also explores the impact of human activities on the natural environment and provides recommendations to ensure ecological sustainability. The article aims to present a scientifically grounded understanding of regional environmental issues.